ULTRAMAFIC ROCKS, GABBROIDS, AND TITANOMAGNETITE ORE AT KACHKANAR, THE CENTRAL URALS: AN INTEGRATED PETROLOGICAL MODEL - Popov V.S.; Nikiforova N.F. (My University, 2004)
Like other massifs of the Platinum Belt in the Urals, the Kachkanar massif is composed of ultramafic rocks and younger gabbroids. The older association of dunite with olivine and magnetite clinopyroxenites is related to the wehrlite mantle source. The primary magma was a product of the 13%-melting of wehrlite and fitted olivine clinopyroxenite with Fe/Mg = 0.45 in composition. Clinopyroxene was completely consumed by the partial melting of the wehrlitic mantle, so that the restite consisted of dunite. The further melt fractionation resulted in the separation of the Fe-rich residual liquid that solidified as magnetite clinopyroxenite; the last portion of the liquid phase could be represented by oxide ore melt. A hot mixture of Fe-rich liquid and Mg-rich cumulates was squeezed upward carrying the blocks and sheets of the dunitic restite. Olivinite and magnetite wehrlite were formed as a result of impregnation of dunite bodies with residual melt. The younger gabbroic association is related to the lherzolite mantle source that underwent a partial melting according to the scheme: lherzolite = picrobasalt + harzburgite. The ascent of the mantle-derived magmatic material was accompanied by the heating of metavolcanics in the Earth's crust and their anatectic fusion with a separation of the plagiogranite melt batches. The water-bearing felsic melt mixed with the water-deficient basic liquid, forming a hybrid gabbronorite magma. Its further fractionation was largely provided by the separation of clinopyroxene and titanomagnetite. The residual liquid crystallized as plagioclasite dikes. The basic rocks and partly clinopyroxenites of the Kachkanar massif underwent the hydrous metamorphism with the participation of metamorphic water solutions released from the country metavolcanics heated approximately to 700degreesC. The peak of hydrous metamorphism fell during the time when the late basic, plagioclasite, and plagiogranite dikes were emplaced.